Ciliary signaling proteins are mislocalized in the brains of Bardet-Biedl syndrome 1-null mice - Stubbs, Toneisha; Bingman, James I.; Besse, Jason; Mykytyn, Kirk (Frontiers in Cell and Developmental Biology, 2023)
In the brain, primary cilia are found on most, if not all, central neurons. The importance of neuronal cilia is underscored by the fact that human diseases caused by primary cilia dysfunction, which are known as ciliopathies, are associated with neuropathologies, including neuropsychiatric disorders and learning and memory deficits. Neuronal cilia are enriched for certain G protein-coupled receptors (GPCRs) and their downstream effectors, suggesting they sense and respond to neuromodulators in the extracellular milieu. GPCR ciliary localization is disrupted in neurons from mouse models of the ciliopathy Bardet-Biedl syndrome (BBS), with GPCRs failing to localize to cilia, indicating the BBS proteins are required for trafficking of GPCRs into neuronal cilia. Yet, dopamine receptor 1 accumulates in cilia in the absence of BBS proteins, suggesting BBS proteins are required for normal ciliary import and export. To further explore the roles of the BBS proteins in neuronal cilia, we examined localization of ciliary signaling proteins in a new constitutive Bbs1 knockout mouse model. Interestingly, we find that two additional ciliary GPCRs (Gpr161 and Gpr19) abnormally accumulate in cilia on BBS neurons. In addition, we find that the GPCR signaling protein β-arrestin accumulates in a subset of cilia in the brain, suggesting the presence of additional unidentified ciliary GPCRs. These results confirm the importance of the BBS proteins in establishing ciliary GPCR pathways and indicate that loss of Bbs1 leads to complex changes in the localization of signaling proteins in the brain.